COVID-19 and procrastination: The struggle to stay motivated in a pandemic - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
COVID-19 has led to the cancellation of countless internships, travel plans, summer jobs, music concerts and festivals, graduations, conferences, you name it. Fixed deadlines have become fluid, and both short-term and long-term goals are presently at the mercy of something far beyond our control. In the face of a global pandemic, we may find ourselves wondering, “Why bother planning for anything anyway?" Yet this very mindset is the crux of the coronavirus procrastination problem, says CHARDONNAY NEEDLER.